Choline metabolism and its implications in cancer - Yao, Nan; Li, Wenqiang; Xu, Guoshuai; Duan, Ning; Yu, Guoyong; Qu, Jun (Frontiers in Oncology, 2023)
Choline, a quintessential quaternary ammonium compound, plays a cardinal role in several pivotal biological mechanisms, chiefly in safeguarding cell membrane integrity, orchestrating methylation reactions, and synthesizing vital neurotransmitters. This systematic review meticulously dissects the complex interplay between choline metabolism and its profound implications in oncology. The exposition is stratified into three salient dimensions: Initially, we delve into the intricacies of choline metabolism, accentuating its indispensability in cellular physiology, the enzymatic labyrinth governing its flux, and the pivotal cellular import mechanisms. Subsequently, we elucidate the contemporary comprehension of choline metabolism in the cancer paradigm, traversing its influence from inception to the intricate metamorphosis during oncogenic progression, further compounded by dysregulated enzyme activities and aberrant signaling cascades. Conclusively, we illuminate the burgeoning potential of choline-centric metabolic imaging modalities, notably magnetic resonance spectroscopy (MRS) and positron emission tomography (PET), as avant-garde tools for cancer diagnostics and therapeutic trajectory monitoring. Synoptically, the nuanced perturbations in choline metabolism in neoplastic entities unfurl critical insights, potentially heralding paradigm shifts in diagnostic and therapeutic oncological stratagems. A deeper foray into this realm is anticipated to fortify our molecular understanding and refine intervention modalities in cancer theranostics.